The Effective Tooth Brushing Parameter of Different Case Studies: A Literature Review - Sanusi, Shahmir Hayyan; Safian, Mohd Aniq (Research Progress in Mechanical and Manufacturing Engineering, 2021)
Tooth decay and non-carious cervical lesions (NCCLs) are common oral complications that deteriorates peoples’ oral health, which without any proper understanding to mitigate the issues could eventually worsen the complications.  The main objective in the journal review is to provide an overview on the effects of different configuration from both toothbrush and toothpaste as well as understanding the interaction between these tooth cleaning components’. In this review, the parameters that affect toothbrushes are; (the type of brushes head configuration, the diameter and stiffness), while for toothpastes; (RDA- value, concentration, different abrasives) and for physical factors; (brushing loads, speed, temperature). Each of these parameters have an effects on the efficiency of tooth cleaning process.